MENTORING BAITUL MAL GAMPONG LANCANG GARAM TOWARDS PROFESSIONAL PHILANTHROPY - Falahuddin; Fuadi; Mukhlish M. Nur; Rico Nurilham; Reza Juanda; Ramadhan Razali (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Community Service Activities with the Environmental Village Development scheme were carried out in Lancang Garam Village, Banda Sakti District, Lhokseumawe City with the target of Baitul Maal Gampong. This organization is part of the gampong government which will improve the economy and welfare of Lancang Garam residents if the management of ziswaf funds (zakat, infaq, alms and waqf) is good. Apart from that, the current condition of Baitul Maal is faced with many problems, such as the problem of lack of public trust, as a result of an ineffective work ethic, and disharmony within the Baitul Maal institutional unit itself. Baitul Maal Gampong Lancang Garam's openness for future development is very good, they really hope for assistance. However, the aim of community service with the Environmental Village Development scheme is to provide understanding and help the community by maximizing assistance in this service. The PKM Team uses the PAR (Participation Action Research) method as a method and approach in this service. Where the three pillars of PAR such as research methodology, action dimensions and participation dimensions are very relevant to use. After providing assistance through this method, the Unimal PKM Team hopes that the structural and non-structural Baitul Maal gampong bodies in Lhokseumawe City will be able to understand and implement it. As a result, professional constructivity will be realized in Baitul Maal Gampong Lancang Garam. The activity implementation method consists of three stages. The first preparation stage includes pre-survey, team formation, making and submitting proposals, coordinating teams and partners as well as preparing training tools and materials. The second stage is the implementation of the program in the form of providing an understanding of the coaching and training program with work aspects, increasing employee understanding of the management of Baitul Maal gampong as well as digital-based training related to muamalah fiqh improvisation, and this implementation is carried out through counseling (presentation of material) and discussions. The third stage is the evaluation and reporting stage. Evaluation is carried out by comparing the conditions of partners before and after the implementation of mentoring and coaching in the form of all the time discussions. comparing the conditions of partners before and after implementing mentoring and coaching in the form of all the time discussions.